Innovation vector of reconciliation and optimization of social and economic interests of society for potential of industrialized regions - Комарніцький, І. О. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The features of influence of innovative vector of the use of potential are in-process investigational on co-ordination and optimization of socio-economic interests of community development at regional level, a mathematical model is worked out and the mechanism of optimization of certain interests of participants of reproduction process is presented.